English language teacher educators’ practices of and approaches to early grade reading instruction in Ethiopia - Elias Kuche Bande; Abate Demissie Gedamu; Wendiyfraw Wanna G/Medihin (Universitas Syiah Kuala, 2026)
English language teachers and students have faced challenges in teaching and learning early-grade reading (EGR) in Ethiopian primary schools. Deficiency of students’ reading skills at primary school can inevitably affect their later learning. To address these issues, an investigation of English language teacher educators’ practices of implementing early-grade reading instruction (EGRI) was required. This study specifically aims to find out the degree to which the teacher educators teach trainee teachers in EGR and the types of instructional approaches they favor in their EGR classrooms. To accomplish the study’s goals, a convergent parallel mixed methods design was employed. Using a purposive sampling technique, 56 educators from three teaching colleges in Ethiopia were included in the study. Questionnaire and observations were used as the instruments to collect data. In addition, three teacher educators’ classes were observed. The data was analyzed using descriptive and inferential statistics as well as thematic analysis. The results showed that teacher educators had moderate practice in teaching reading. In particular, they placed a greater emphasis on phonemic awareness and phonics than on fluency and comprehension training. Regarding the instructional approaches used, the questionnaire data revealed a stronger preference for the balanced approach, whereas the observation data showed a greater reliance on the phonics instructional approach. To better address the issue and provide significant insight into the current theory and practice of EGR, further study is necessary in light of these findings.